Neurocognitive dysfunction in adult cerebellar medulloblastoma. Issue 1 (5th November 2018) - Harrison, Rebecca A.; Kesler, Shelli R.; Johnson, Jason M.; Penas‐Prado, Marta; Sullaway, Catherine M.; Wefel, Jeffrey S.
Abstract: Objective: Impaired neurocognitive function (NCF) is a well‐established consequence of pediatric medulloblastoma (MB) and its treatments. However, the frequency and features of neurocognitive dysfunction in adult‐onset MB patients are largely unknown. Methods: Adult patients (≥ 18 years) with MB who had received formal neurocognitive evaluation ( N  = 27) were identified. Demographic, medical, and treatment histories were extracted from the medical record. Lesion properties on MRI were analyzed and used to evaluate lesion‐symptom mapping further. Demographically adjusted z‐scores were calculated for each neurocognitive test and used to assess impairment frequency. Regression analyses were conducted to identify clinical and paraclinical factors associated with impaired NCF. Results: Mean age of the patient sample was 33 years (SD = 11) at the time of MB diagnosis. Prior therapy included surgical resection (89%), radiation (70%), and chemotherapy (26%). A significant proportion of patients were impaired on tests of verbal learning and memory (32%), executive function (29%), and naming (18%). Age, education, lesion size, time from surgery, and number of chemotherapy cycles had the greatest contribution to test performance in random‐forest regression models. Conclusion: This study identifies frequent impairment of NCF in adult patients with MB, particularly in the domains of learning and memory and executive function. Neurocognitive impairment is influenced by patients' demographic, disease, and treatment history. Further study is warranted to characterize the clinical impact of adult MB more fully.